2021
DOI: 10.15181/rfds.v25i2.1744
|View full text |Cite
|
Sign up to set email alerts
|

Visuomenės ekologinis švietimas darnios plėtros kontekste

Abstract: Kauno statybos ir paslaugų mokymo centras (Lietuva), Aleksandro Stulginskio universitetas (Lietuva) ANOTACIJA Darnia plėtra siekiama išsaugoti ne tik dabarties žmonijos, bet ir ateities kartų galimybes tenkinti savo poreikius, pagrįstus žmogaus vertybėmis. Siekdamas darnios plėtros, žmogus negali ignoruoti socialinių ir ekonominių aspektų, nes tai tampa jo gerovės pagrindu, kartu saugant gamtą su visais jos ištekliais. Ekologinis švietimas padeda suvokti esamos ekologinės problematikos, pasiekusios kritinį lyg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Values influence attitudes toward the environment, perceptions of the consequences of behavior, and acceptance of responsibility, and contribute to environmentally friendly behavior [16]. Jančius [17] observed that values encompass human behavior for the sake of well-being by encouraging reflection on and cultivation of other values and behaviors, and become more effective in building the well-being of oneself and others. Kociszewska [18] identified the domains of cognitive-ecological perception, i.e., knowledge of the processes taking place in nature, of existing risks, of human activities and their negative consequences; a system of values, which are fulfilled by interacting with nature and which encompass life, health, responsibility, work, beauty, harmony, and others; and a domain of rules for action.…”
Section: The Concept and Meaning Of Valuesmentioning
confidence: 99%
“…Values influence attitudes toward the environment, perceptions of the consequences of behavior, and acceptance of responsibility, and contribute to environmentally friendly behavior [16]. Jančius [17] observed that values encompass human behavior for the sake of well-being by encouraging reflection on and cultivation of other values and behaviors, and become more effective in building the well-being of oneself and others. Kociszewska [18] identified the domains of cognitive-ecological perception, i.e., knowledge of the processes taking place in nature, of existing risks, of human activities and their negative consequences; a system of values, which are fulfilled by interacting with nature and which encompass life, health, responsibility, work, beauty, harmony, and others; and a domain of rules for action.…”
Section: The Concept and Meaning Of Valuesmentioning
confidence: 99%